Diffuse Josephson Radiation in Turbulence - Treumann, R. A.; Baumjohann, Wolfgang (Frontiers in Physics, 2021)
The possibility of generating diffuse radiation in extended astronomical media by plasma 4 turbulence is investigated under the assumption that the turbulence can be understood as an ensemble of small-scale magnetic filaments or current sheets forming a texture around a large number of magnetic depletions or voids. On astronomically microscopic scales the dilute high temperature medium (plasma) is to be considered ideally conducting forming a collection of Josephson junctions between two adjacent quasi-superconductors. The oscillation frequency of those junctions is high, from UV into X-rays but depends on the part of the spectrum that contributes to the oscillation. Lowest Josephson frequencies/energies are obtained from the shortest near-dissipation turbulent scales and turbulent electric fields inclined against the junction normal causing broadband Josephson radiation spectra of low intensity. It maximizes at nearly perpendicular electric field and lowest frequency causing weak background radiation.